Pengaruh Kualitas Produk dan Promosi terhadap Kepuasan Deposan di Bank Syariah Indonesia Kantor Cabang Pembantu Setiabudi 2 - Mufhnie Alviani; Faisal Rakhman; Mario Aldo Triadi Abidin (Jurnal Dimamu, 2023)
The background of this study is fluctuations in the number of depositors caused by the still not optimal promotions carried out by banks and the quality of products that still need to be improved. This is important because every product that has good quality and good promotion is expected to lead to satisfaction for customers. This study aims to determine how the influence of product quality and promotion on the satisfaction of depositors at Bank Syariah Indonesia KCP Setiabudi 2 either partially or simultaneously. The object of research is depositors at Bank Syariah Indonesia KCP Setiabudi 2 to find out depositors. While the type of research is quantitative associative, the type of data is primary data so that a questionnaire is needed to find out depositors as objects of research, and the data collection techniques used are observation, interviews, library research. and questionnaire. The results showed that there was a significant effect between product quality on depositor satisfaction of 94,3% with the results of the t-test where the value of tcount> ttable (79.001 > 1.98326), there was a significant influence between promotion on depositor satisfaction of 96,6% with the results of the t-test where the value of tcount > t table (54,290 > 1,98326), and there is a simultaneous influence of product quality and promotion on depositor satisfaction of 98,4% with the F test results where Fcount > Ftable (3201,512 > 3.08).